The Effect of Food Insecurity on the Nutrition Levels of Children in Namatala Slums in Mbale City: A Case Study of Children Under Five Years - Racheal Cynthia Nakawala (Uganda Christian University, 2024)
The study aimed at out the effect of food insecurity on the nutrition levels of children in Namatala slums in Mbale city. It specifically focused on; investigating the economic factors contributing to food insecurity among families residing in Namatala slums, exploring the relationship between food insecurity and the prevalence of malnutrition among children under five years in Namatala slums and examining the role of government in ensuring that children are fed well to prevent malnutrition. The study was carried out using a descriptive survey research design where both quantitative and qualitative research approaches were also used. The data was collected using questionnaires and interviews during the data collection, both purposive and simple random sampling methods were used. A sample size of 5 key informants and 52 parents of the malnourished children below five years were included in the study. According to the study findings, food insecurity in namatala slums is due financial difficulties such as unemployment, poverty, high housing costs and rising food prices which result in food shortage and malnutrition. This has mostly affected children under five. This has caused them to suffer from conditions such as stunted growth and wasting. These issues have been exacerbated by issues such as lack of health education about nutrition and restricted access to health care among others. The government should therefore improve its efforts in various fields such as health education, food programs and more investments in the health sector in order to improve nutritional outcomes of children under five years. Finally, the study the study therefore recommends a strong need for addressing the various economic challenges affecting food security leading to malnutrition among children under five years. Improving government programs for food and networking with various organizations and agencies to address the issue of food insecurity and malnutrition.